2011
DOI: 10.1242/jcs.068254
|View full text |Cite
|
Sign up to set email alerts
|

Loss of p38γ MAPK induces pleiotropic mitotic defects and massive cell death

Abstract: SummaryThe p38 mitogen-activated protein kinase (p38 MAPK) family, which is comprised of four protein isoforms, p38, p38, p38 and p38, forms one of the key MAPK pathways. The p38 MAPKs are implicated in many cellular processes including inflammation, differentiation, cell growth, cell cycle and cell death. The function of p38 MAPKs in mitotic entry has been well established, but their role in mitotic progression has remained controversial. We identify p38 MAPK as a modulator of mitotic progression and mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…In response to Ras signaling, p38␣ phosphorylation is increased, and phosphorylated p38␣ then functions as a tumor suppressor in vitro (12,13) and in vivo (14,15), whereas p38␥ expression is increased, and resulting p38␥ in turn promotes the oncogenic process independently of (16 -18) and dependent on phosphorylation (19,20). In stress response, although p38␥ is similarly activated as pro-apoptotic p38␣, it plays an anti-apoptotic role under certain conditions (17,(21)(22)(23)(24). Among MAPK family proteins, p38␥ is the only member whose expression is induced during differentiation (25), transformation, and/or invasion (16,18,19).…”
mentioning
confidence: 99%
“…In response to Ras signaling, p38␣ phosphorylation is increased, and phosphorylated p38␣ then functions as a tumor suppressor in vitro (12,13) and in vivo (14,15), whereas p38␥ expression is increased, and resulting p38␥ in turn promotes the oncogenic process independently of (16 -18) and dependent on phosphorylation (19,20). In stress response, although p38␥ is similarly activated as pro-apoptotic p38␣, it plays an anti-apoptotic role under certain conditions (17,(21)(22)(23)(24). Among MAPK family proteins, p38␥ is the only member whose expression is induced during differentiation (25), transformation, and/or invasion (16,18,19).…”
mentioning
confidence: 99%
“…Our observation revealed that p38γ MAPK knockdown in 4T1 cells led to significant decrease of cell proliferation, a phenomenon also observed in Hela cells. 5 Concomitantly, we observed decreased cell migration and invasion in 4T1 cell with p38γ MAPK depletion. Furthermore, a xenografting experiment showed a significant shrinkage of tumor formation along with marked decrease of lung metastasis, suggesting that the decreased cell migration and invasion or metastasis is mostly due to the effect of p38γ MAPK on cell survival.…”
mentioning
confidence: 58%
“…The AllStars Hs Cell Death Control siRNA is used as a positive transfection. [41][42][43][44][45] A total of 25,000 MDA-MB-231 cells were added to two 24-well plates; one 24-well plate each for long-term monitoring of colony growth by live cell imaging with IncuCyte ZOOM ® (Essen Instruments, Ann Arbor, MI, USA).…”
Section: Sirna Transfection Efficiencymentioning
confidence: 99%
“…The employed cell-killing siRNA has been used previously as a positive control for transfection. [41][42][43][44][45] The aim of the experiment was to investigate transfection efficiency of MSN nanocarriers in MDA-MB-231 cells; therefore, we used a very general siRNA transfection approach rather than selecting some specific cellular target. The transfection efficacy was benchmarked against a commercial transfection agent, Lipofectamine RNAiMax, as a positive (cell death) control.…”
Section: Functional Assay For the Delivery Of Biologically Active Sirmentioning
confidence: 99%
See 1 more Smart Citation